2022
DOI: 10.1021/acsmacrolett.2c00523
|View full text |Cite
|
Sign up to set email alerts
|

Linear Cyclobutane-Containing Polymer Synthesis via [2 + 2] Photopolymerization in an Unconfined Environment under Visible Light

Abstract: The [2 + 2] photopolymerization of diolefinic monomers is an appealing approach for the construction of polymeric materials. Herein, we demonstrate that the establishment of an effective donor–acceptor conjugation by introducing electron-donating alkoxy groups at appropriate positions of the benzene ring could activate p-phenylenediacrylate (PDA), thus enabling the development of the first solution [2 + 2] photopolymerization of such monomers under the irradiation of visible light. Variation on the alkoxy grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…SEC measurements showed that molecular weight increased from 2.9 to 4.6 kDa after UV irradiation of Den-TPA in water at 20 °C for 5 min (Figure S3). The above results demonstrate the cinnamate moieties in Den-TPA were efficiently photodimerized below its T cp to form soluble oligo­(dendrimer)­s, which is similar as [2 + 2] photocycloaddition polymerization of diolefin monomers in solutions. , It is worthy to mention that the photocycloaddition of Den-TPA below its T cp did not generate the well-defined microgels despite the amphiphilic aggregation in water. This may be because the associative interaction among Den-TPA molecules below T cp is so weak and dynamic that cannot facilitate the microgel formation .…”
Section: Resultsmentioning
confidence: 99%
“…SEC measurements showed that molecular weight increased from 2.9 to 4.6 kDa after UV irradiation of Den-TPA in water at 20 °C for 5 min (Figure S3). The above results demonstrate the cinnamate moieties in Den-TPA were efficiently photodimerized below its T cp to form soluble oligo­(dendrimer)­s, which is similar as [2 + 2] photocycloaddition polymerization of diolefin monomers in solutions. , It is worthy to mention that the photocycloaddition of Den-TPA below its T cp did not generate the well-defined microgels despite the amphiphilic aggregation in water. This may be because the associative interaction among Den-TPA molecules below T cp is so weak and dynamic that cannot facilitate the microgel formation .…”
Section: Resultsmentioning
confidence: 99%
“…Photocatalysis has attracted great attention where the light is abundant, mild, cheap, environmentally friendly, and capable of spatiotemporal control. [ 21‐26 ] In recent years, the focus has been placed on adapting photocatalytic reactions in polymer synthesis, such as post‐modification or polymerization, [ 22,27‐30 ] and the organic reaction needs to be highly reactive and efficient due to the reduced mobility of active species in the polymer chains. [ 22 ] Therefore, some efficient photo‐induced reactions have been used to post‐modify polymers.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…However, in solution and bulk samples of organic molecules, it is difficult to obtain the target photoreaction products by controlling the specific orientations and distances of CC double bonds, and only a few types of photocycloaddition products can be generated. 8–10…”
Section: Introductionmentioning
confidence: 99%
“…However, in solution and bulk samples of organic molecules, it is difficult to obtain the target photoreaction products by controlling the specific orientations and distances of CvC double bonds, and only a few types of photocycloaddition products can be generated. [8][9][10] Coordination polymers (CPs) are constructed of metal ions or metal cluster cores that are coordinated by organic ligands, and they are highly crystalline. 11,12 Upon self-assembly, the position of each atom in these structures is well determined and can be fine-tuned by structural design.…”
mentioning
confidence: 99%